FAR1-RELATED SEQUENCE (FRS) and FRS-RELATED FACTOR (FRF) Family Proteins in Arabidopsis Growth and Development - Ma, Lin; Li, Gang (Frontiers in Plant Science, 2018)
Transposable elements make important contributions to adaptation and evolution of their host genomes. The well-characterized transposase-derived transcription factor FAR-RED ELONGATED HYPOCOTYLS 3 (FHY3) and its homologue FAR-RED IMPAIRED RESPONSE1 (FAR1) have crucial functions in plant growth and development. In addition, FHY3 and FAR1 are the founding members of the FRS (FAR1-RELATED SEQUENCE) and FRF (FRS-RELATED FACTOR) families, which are conserved among land plants. Although the coding sequences of many putative FRS and FRF orthologs have been found in various clades of angiosperms, their physiological functions remain elusive. Here, we summarize recent progress towards characterizing the molecular mechanisms of FHY3 and FAR1, as well as other FRS-FRF family proteins, examining their roles in regulating plant growth and development. This review also suggests future directions for further functional characterization of other FRS-FRF family proteins in plants.